Estudo de associação dos SNPs do Gene Smoothned à suceptibilidade de Câncer Basocelular na população Paraibana - Oliveira, Paulo Junio Ribeiro de (2018)
The Cancer to basocelular is most common enters all the types of cancer; appearing in the layer deepest of the epidermis, generally it is not mortal and rare it provokes metástase. However if treated adequately they cannot cause damages in great portions of fabric adjacent, with consequent disfigurament of the patients. Its cause if of mainly for intense or accumulated solar exposition throughout the life; but also it can occur for contact with chemical products, exposition to the radiation, chronic illnesses of skin, among others factors, being very difficult to point an only cause. Some ways of signalling are related with the CBC development; the way Hedgehog, very active in the embryonic phase, possesss little function in the adult phase and when if it finds super express possesss carcinogênica activity. This abnormal activity has been related with CBCs, with mutations that activate protoncogene SMO. The present study it carried through the genotyping of SNPs RS769334511 (A>C), RS749414966 (T>C) in gene SMO, 100 fabric samples paraffined of patients diagnosised with carcinoma to basocelular. The results had been gotten by means of the method of genotipagem Didesoxi Only Specific Alelo PCR- DSASP. The SNPs rs769334511 and rs749414966 of gene SMO had statistical presented significant association to the susceptibilidade and the risk to develop CBC. SNPs RS769334511 and RS749414966 SMO associates to the susceptibilidade to the development of the CBC in the analyzed samples are potential molecular markers.